ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI WAKTU KELULUSAN MAHASISWA DENGAN MENGGUNAKAN METODE GOMPIT (Studi Kasus: Mahasiswa Fakultas MIPA Universitas Udayana) - ARIANI, NI KOMANG DEBY; SUMARJAYA, I WAYAN; BAGUS OKA, TJOKORDA (E-Jurnal Matematika; Vol 2 No 3 (2013), 2013)
The aims of this research analyzed the factors affecting the period of the students’ graduation based on GPA at Faculty of Mathematics and Natural Science, Udayana University by using gompit regression. This data strongly indicates unbalanced between students who graduated on time and students who graduated not on time. The result of this study indicates that the graduation of the students based on the GPA categorization satisfied all of the independent variables was not significant. Meanwhile, for the graduation of the students based on the GPA categorization was highly satisfied. There are four dependent variables which are significant, such as: gender, study program, region, and the final assignment accomplishment period. Moreover, for the students’ graduation based on the GPA categorization with praises, there were two independent variables which were significant: region and the final assignment accomplishment period.
Keywords: gompit method; graduate point average (GPA); students’ graduation period